Baseline blood pressure control in Hispanics: characteristics of Hispanics in the Systolic Blood Pressure Intervention Trial. Issue 2 (14th November 2016) - Rodriguez, Carlos J.; Still, Carolyn H.; Garcia, Katelyn R.; Wagenknecht, Lynne; White, Suzanne; Bates, Jeffrey T.; Del Cid, Margareth V.; Lioudis, Michael; Lopez Barrera, Nieves; Moreyra, Abel; Punzi, Henry; Ringer, Robert J.; et al.
Abstract : The Systolic Blood Pressure Intervention Trial (SPRINT) tested whether a systolic blood pressure (SBP) value <120 mm Hg reduces adverse clinical outcomes compared with the goal of <140 mm Hg. Here the authors describe the baseline characteristics of Hispanic participants in SPRINT. Nondiabetic hypertensive patients 50 years and older with SBP 130–180 mm Hg taking zero to four blood pressure (BP) medications were enrolled from the mainland United States and Puerto Rico. Cross‐sectional, bivariate analysis was employed comparing sociodemographic and clinical factors in Hispanics vs non‐Hispanics. Multivariable logistic regression models restricted to Hispanics were used to identify factors associated with achieved BP control (SBP <140 mm Hg and diastolic BP <90 mm Hg) at baseline. Eleven percent (n=984) of SPRINT participants were Hispanic; 56% (n=549) of Hispanics were living in Puerto Rico and the remainder were living on the US mainland. Hispanics overall were younger, more often female, less likely to live alone, and more likely to have lower education and be uninsured, although just as likely to be employed compared with non‐Hispanics. BP control was not different between Hispanics vs non‐Hispanics at baseline. However, a significantly higher percentage of Hispanics on the US mainland (compared with Hispanics in Puerto Rico) had controlled BP. BP control was independently associated with cardiovascular disease history and functional status among Hispanics, specifically those living in Puerto Rico, whereas functional status was the only independent predictor of BP control identified among mainland Hispanics. These findings highlight the diversity of the SPRINT population. It remains to be seen whether factors identified among Hispanics impact intervention goals and subsequent clinical outcomes.